BI-2536 and BI-6727, dual Polo-like kinase/bromodomain inhibitors, effectively reactivate latent HIV-1 - Jin Gohda (Nature Portfolio, 2018)
Abstract HIV-1 latent reservoirs harbouring silenced but replication-competent proviruses are a major obstacle against viral eradication in infected patients. The “shock and kill” strategy aims to reactivate latent provirus with latency reversing agents (LRAs) in the presence of antiretroviral drugs, necessitating the development of effective and efficient LRAs. We screened a chemical library for potential LRAs and identified two dual Polo-like kinase (PLK)/bromodomain inhibitors, BI-2536 and BI-6727 (volasertib), which are currently undergoing clinical trials against various cancers. BI-2536 and BI-6727 significantly reactivated silenced HIV-1 provirus at both the mRNA and protein level in two latently infected model cell lines (ACH2 and U1). BI-2536 dramatically reactivated transcription of latent HIV-1 provirus in peripheral blood mononuclear cells derived from infected patients. Long terminal repeat activation by the inhibitors was associated with bromodomain rather than PLK inhibition. We also found that BI-2536 synergistically activates the latent provirus in combination with SAHA, a histone deacetylase inhibitor, or the non-tumour-promoting phorbol ester prostratin. Our findings strongly suggest that BI-2536 and BI-6727 are potent LRAs for the “shock and kill” HIV-1 eradication strategy.